KONTRIBUSI KOMPENSASI DAN MOTIVASI TERHADAP KINERJA KARYAWAN BTM SAKINATUL UMMAH LAMPUNG TIMUR - Bakhri, Syaiful; Azizah, Viona Nur; Dede, Dede; Fauzi, Fauzi (FACULTY OF ECONOMICS AND BUSINESS FLORES UNIVERSITY, 2025)
The economic movement of a nation is actually supported by various sectors, including Islamic microfinance institutions. This study aims to determine whether compensation and motivation have a positive effect on employee performance at Baitut Tamwil Muhammadiyah (BTM) Braja Harjosari, East Lampung. The population in this study were all employees of BTM Sakinatul Ummah Braja Harjosari, East Lampung. Samples were taken using a saturated sampling technique of 18 people. Data analysis procedures used for statistical analysis include t-test, F-test, coefficient of determination (R2), and multiple linear regression tests. The results of the study indicate that (1) Compensation has a positive and significant effect on employee performance with a significance value of 0.026 <0.05, (2) Motivation does not have a positive effect on employee performance with a significance value of 0.192> 0.05 (4) Compensation and motivation have a positive and significant effect on employee performance simultaneously with a significance value of 0.003 <0.05.